Obtenção de corpos cerâmicos porosos de TiO2 para o emprego como biomateriais - Bertoni, Patrícia Maria Vieira (2014)
This work was carried out in order to verify the feasibility of obtaining TiO2 porous ceramic material with specific characteristics of porosity for employment as a biomaterial, through the method of shaping by starch consolidation. Thus samples with different solids and starch contents ranging from 10 to 50% were fabricated. The choice of titanium dioxide is due to its well known properties of biocompatibility, due to its structural similarity with bone tissue, low cost and ability to sterilization. The ceramic bodies were pre-sintered at 1200 ° C and sintered at 1400 ° C. The characterization of the ceramic pieces was taken by the essay based on Archimedes' principle, where we got the bulk density, porosity and absorption capacity of the pieces. The actual densities of the mass losses were determined during processing of the material, ie the green body, the pre-sintered body and the sintered body. The porosity was also evaluated by scanning electron microscopy and by means of liquid piercing testing. The characterization of mechanical resistance was performed using the assay of three points in order to guide the use of the material obtained. The material presented porosity from 17 % to 48 %, varying according to the percentage of starch in the suspension. The decrease in pre-sintering at 1200 ° C was around 11 % and after sintering at 1400 ° C showed values ​​around 20 %. The pores of the material obtained had diameters from 100 to 400 цm. Also the pore interconnectivity can be verified. Thus, the technique adopted for obtaining proved effective in obtaining specific porosity for biomedical purposes.